2023
DOI: 10.24857/rgsa.v18n3-007
|View full text |Cite
|
Sign up to set email alerts
|

Between the Power of the "Satanic Mill of Production" and the "Counter-Movements" for Land Reform

Ethol Exime,
Cleoson Moura Dos Reis,
Aline Costa Gonzalez
et al.

Abstract: Objective: The aim of the essay is to discuss the agrarian issue in Brazil, articulating it in the mainstream of sustainable development, as an opportunity to democratize access and use of land, and especially to inhibit chronic problems that generate opulence and deprivation of freedoms, such as those emphasized by the COVID-19 crisis.   Theoretical framework: It is based on the perspectives of two renowned researchers, Navarro and Medeiros. While Navarro questions the options for agrarian reform in democrati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 24 publications
0
1
0
Order By: Relevance
“…The Provincial Government must protect other customary groups that have not been affected by land confiscation (Blache, 2019). The study of Exime et al, (2023) revealed cases of land confiscation in Brazil that the abuse of power to invade citizen land entitled to that space is a crime and suggested Siki, N., Samudra, A., A., Satispi, E. (2024). Conflict Situation and Proposals for Resolving Customary Land Conflicts in East Nusa Tenggara, Indonesia solving it through land reform.…”
Section: Alternative Route To Solutionmentioning
confidence: 99%
“…The Provincial Government must protect other customary groups that have not been affected by land confiscation (Blache, 2019). The study of Exime et al, (2023) revealed cases of land confiscation in Brazil that the abuse of power to invade citizen land entitled to that space is a crime and suggested Siki, N., Samudra, A., A., Satispi, E. (2024). Conflict Situation and Proposals for Resolving Customary Land Conflicts in East Nusa Tenggara, Indonesia solving it through land reform.…”
Section: Alternative Route To Solutionmentioning
confidence: 99%